Development of physical test norms for early age Pencak Silat - Dewi Nurhidayah; Yudik Prasetyo; Panggung Sutapa; Fitri Agung Nanda; Dinan Mitsalina; Ela Yuliana (IP Iermakov S.S., 2024)
Background and Study Aim. The evaluation serves as a cornerstone in the continuous improvement of sports, significantly relying on the analysis of measurement data. The primary objective of this research is to develop tailored norms for physical tests specifically designed for early-age Pencak Silat practitioners. Material and Methods. The development of the test consisted of several key stages: design of the instrument, testing of the instrument, and finally, assembly of the instrument. The study included a total of 210 participants, with a breakdown of 111 male and 109 female martial artists. The techniques for data collection involved a variety of tests and measurements. The instruments used in this research included: sit-and-reach test for assessing flexibility, 30-meter sprint for speed evaluation, side step test for agility, sit-ups for abdominal strength, push-ups for arm and chest strength, wall sit test for leg muscle strength, and beep test for cardiovascular endurance. Data analysis was performed using a technique that grouped values into five standard categories, aided by the use of Microsoft Excel. Results. The findings of the study led to the establishment of norms for each component of the physical tests tailored to early-age Pencak Silat practitioners. These components have been classified into five distinct levels: very poor, poor, average, good, and excellent. Conclusions. The outcomes of this research facilitate the development of specific norms for each test item, incorporating weighting for every physical test component. These weightings have been meticulously adjusted in accordance with the primary energy systems utilized in the sport of Pencak Silat.